Lupus mastitis: A rare breast cancer differential diagnosis. Issue 7 (9th July 2021) - Pimentel, Alice; Moreira, Ana; Silva, Sofia; Lages, Rita; Noronha, Joana
Abstract: Lupus mastitis is an uncommon SLE breast manifestation. Clinically, it can present itself as a malignant‐like mass. Therefore, a tissue biopsy is warranted to confirm the diagnosis. The treatment of this condition is pharmacological and directed to the underlying disease. The rarity of this entity demands a high degree of suspicion. Abstract : Lupus mastitis is an uncommon SLE breast manifestation. Clinically, it can present itself as a malignant‐like mass. Therefore, a tissue biopsy is warranted to confirm the diagnosis. The treatment of this condition is pharmacological and directed to the underlying disease. The rarity of this entity demands a high degree of suspicion.